Enfermagem forense em cursos de graduação em enfermagem - Souza, Jhuliano Silva Ramos De (2020)
Undergraduate nursing courses are governed by the National Curriculum Guidelines for the Nursing Undergraduate Course, which bring the nurse's profile, curriculum content, competencies and skills, among others. Forensic nursing is a science that links nursing care with forensic aspects, in which the professional will provide assistance to victims, aggressors, family members and the community involved in cases of violence. This study aimed to analyze the syllabus content of forensic nursing in the pedagogical projects of undergraduate nursing courses. This is a quantitative, descriptive and exploratory study, in which coordinators of nursing courses from 88 public and private Higher Education Institutions participated, through a dichotomous questionnaire and open questions called “Questionnaire for Tracking Disciplines and Content of Forensic Nursing in Undergraduate Nursing Courses”, developed by the researchers and passed empirical and content validation by judges, according to Pasquali's methodological framework. Data collection was carried out between April and August 2019, using the Google Forms platform. For data analysis, the Software Package for the Social Science was used for descriptive and inferential statistics, and Software R, for Fisher's Exact test for independent variables (positive and negative responses) and dependent variables (region, duration and course type). The project was approved by the Research Ethics Committee of the Federal University of Alfenas under Opinion: 2,893,206, CAAE: 97046718.0.0000.5142. Of the Higher Education Institutions surveyed, the disciplines of forensic nursing and violence are rarely offered in the curriculum, there was a predominance of private Higher Education Institutions located in the Southeast and South regions. Regarding forensic nursing content, evaluation and intervention in physical, sexual and psychological violence and those that appeared least were the forensic protocols, assistance to the aggressors, collection of biological DNA material, preservation of the collection of forensic remains and forensic evidence in hospital services. The disciplines that most presented forensic nursing content were child and adolescent health, women's health, urgency and emergency and mental health. It was possible to identify that the forensic nursing syllabus contents were predominantly offered in private Higher Education Institutions and in the Southeast region. The knowledge gaps considered were nursing care for perpetrators, nursing practice at the Legal Medical Institute, collection, preservation of forensic remains, forensic protocols, expert reports. The possibility of having a specific discipline on Forensic Nursing in the curricula is considered, due to the breadth of areas of expertise, because it involves the life cycle and the diversity of content related to violence and the consequences of violence in the people involved.